2014
DOI: 10.1596/1813-9450-7066
|View full text |Cite
|
Sign up to set email alerts
|

Non-Farm Enterprises in Rural Africa: New Empirical Evidence

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 74 publications
1
49
0
Order By: Relevance
“…Compared to advanced economies the differences are even greater (Harrison et al, 2014). Also here firm-level heterogeneity in productivity levels is found (Nagler and Naudé, 2014). Exporting, urban-based, formal and larger non-agricultural firms tend to be overall more productive (Rijkers et al, 2010;Söderbom and Teal, 2004;Van Biesebroeck, 2005).…”
Section: Labour Productivity In Africamentioning
confidence: 64%
See 4 more Smart Citations
“…Compared to advanced economies the differences are even greater (Harrison et al, 2014). Also here firm-level heterogeneity in productivity levels is found (Nagler and Naudé, 2014). Exporting, urban-based, formal and larger non-agricultural firms tend to be overall more productive (Rijkers et al, 2010;Söderbom and Teal, 2004;Van Biesebroeck, 2005).…”
Section: Labour Productivity In Africamentioning
confidence: 64%
“…Winters et al, 2009 andDavis et al, 2010). More recently however findings by Nagler and Naudé (2014) and Davis et al (2014) have found otherwise.…”
Section: Household Enterprisesmentioning
confidence: 90%
See 3 more Smart Citations